2017
DOI: 10.1177/0017896917700681
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a multi-component physical activity programme in low-income elementary schools

Abstract: Objective: To identify the effects of a structured and multifaceted physical activity and recess intervention on student and adult behaviour in school. Design: Mixed-methods and community-based participatory approach. Setting: Large, urban, low-income school district in the USA. Methods: Data were collected at three time points over a 1-year period. Sources included recess observations at four elementary schools, in-class behavioural observations of fifth-grade students ( n = 21) and focus groups with fourth- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…Individuals who regularly experience negative feelings of receiving cruel or unfair treatment are likely to retaliate aggressively due to continual exposure to these sentiments [57]. Participation in physical activity can be a protective factor against this response as participants become accustomed to negative physical and emotional contact and learn to manage their feelings and deal with ideas of physical violence [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who regularly experience negative feelings of receiving cruel or unfair treatment are likely to retaliate aggressively due to continual exposure to these sentiments [57]. Participation in physical activity can be a protective factor against this response as participants become accustomed to negative physical and emotional contact and learn to manage their feelings and deal with ideas of physical violence [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, if children are active in an environment that includes high levels of bullying and anti-social behavior, it is likely that PA alone will not contribute positively to their social development [15]. Moreover, research has shown children's experiences of recess differ greatly, and may be effected by equity of space and equipment use [16], gender [17], adult engagement [7], and social status [18]. Thus, comprehensive and thorough evaluation of how the environment shapes various outcomes is paramount to understanding how recess contributes to the health and wellbeing of children in schools.…”
Section: Discussionmentioning
confidence: 99%
“…By placing these adults on the playground, and training teachers to engage in recess facilitation, changes should be seen in the GRF-OT adult supervision and engagement items. Previous research has shown that total adult-student interactions, and positive adult-student interactions increase overtime with Playworks, while punishment from adults on the playground decreases over time [7]. During recesses, Playworks coaches provide equipment, lead and organize games and activities that empower students and school staff to take control of the recess environment in a positive manner.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that environmental factors affect children's access to physical activity opportunities in urban and lowincome school systems. Notably, bullying and aggressive behavior have been reported on the playground at urban elementary schools (9,10), which could result in fewer opportunities for students.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, behavioral observations have suggested that bullying regularly takes place during recess periods (10). In terms of physical activity during recess, children have specifically discussed conflict as a barrier to play for boys and girls alike.…”
Section: Introductionmentioning
confidence: 99%